Mahadma Gandhi and Netaji Subbash Chandra Bose from Political Philosophy Perspective - Pham Ngoc Thuy, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Mahatma Gandhi and Netaji Subhas Chandra Bose were two legendary personalities, gigantic in their political moral and ethical stature. Both of them were two worthy sons of Mother India but in many aspects, they were so different from each other. However, among all the Indian Freedom Fighters, Netaji Subhas Chandra Bose’s ranking concerning his contribution to Indian freedom struggle and popularity is next only to Mahatma Gandhi. Interestingly, historians, military strategists, anti-colonialists and political scientists have had the veteran revolutionary as a subject of serious academic discussions. “Tum mujhe khoon do mein tumhein azaadi doon ga” - These words were uttered by the great revolutionary of colonial time, Netaji Subhas Chandra Bose. The intention behind the statement comes from Netaji's idea that India could never get freedom through peaceful means unlike Mahatma Gandhi (Mohandas Karamchand Gandhi), whose ideology was more non-violent. On one hand there was Subhas Chandra Bose and on the other hand there was GANDHI. The relationship between these two characters is very important. In this paper, I try to analyse the differences and even similarities between two great figures of India in term of political philosophy.Received 9thDecember 2020; Revised 2nd March 2021; Accepted 20th March 2021